2008
DOI: 10.1007/s00405-008-0813-7
|View full text |Cite
|
Sign up to set email alerts
|

UPPP combined with radiofrequency thermotherapy of the tongue base for the treatment of obstructive sleep apnea syndrome

Abstract: The third sentence of the second paragraph in "Discussion" should read:Adding RFTB to UPPP gave an increase in objective success rate of 17.2%, from 37.9 to 55.1% for Friedman stage II patients and an increase of 24.9%, from 8.1 to 33.0% for stage III patients.The online version of the original article can be found under

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Friedman et al 14 also reported a worse success rate (41.0% vs 51.7%), probably because his patients had a higher mean AHI than ours (43.9 Ϯ 23.7 vs 32.5 Ϯ 8.0, respectively) and were treated with a lower energy level (3000-9000 J vs 9000 J). Other groups [15][16][17] reported an overall success rate similar to ours (50%, 53.6%, and 49%, respectively, vs 51.7%).…”
Section: Discussionsupporting
confidence: 85%
“…Friedman et al 14 also reported a worse success rate (41.0% vs 51.7%), probably because his patients had a higher mean AHI than ours (43.9 Ϯ 23.7 vs 32.5 Ϯ 8.0, respectively) and were treated with a lower energy level (3000-9000 J vs 9000 J). Other groups [15][16][17] reported an overall success rate similar to ours (50%, 53.6%, and 49%, respectively, vs 51.7%).…”
Section: Discussionsupporting
confidence: 85%
“…The apnea hypopnea index (AHI) is the mean number of apneas and hypopneas per hour of sleep and signifies the severity of OSAS. An AHI of 5 -15 indicates mild OSAS, AHI of 15-30 is moderate OSAS, and AHI >30 is severe OSAS, as assessed by polysomnography 12,13 .…”
Section: Sleep Study and Polysomnography Scoringmentioning
confidence: 99%